Perancangan Ergonomis Troli Barang Menggunakan Metode French: Pendekatan Antropometri, Analisis Keselamatan, dan Kelayakan Ekonomi pada Industri Kecil Menengah - Anang Priambudi; Rixza Brilians Aldiansyah; Afny Dwi Rahma; Aldila Agil Mahardhika; Novi Marlyana (PT. Hasba Edukasi Mandiri, 2026)
Manual Material Handling (MMH) activities at small and medium industries (SMI) frequently expose workers to musculoskeletal disorder (MSD) risks due to the absence of ergonomic assistive tools. This study presents the systematic design and development of a goods trolley for IKM Virgo Snack using the French product design method integrated with multiple Body of Knowledge (BOK) perspectives: Product Design and Development, Ergonomics and Human Factors, Design and Manufacturing Engineering, Occupational Safety, and Engineering Economics Analysis. Anthropometric data (n=30) covering standing elbow height, shoulder width, and grip diameter were collected and subjected to adequacy, uniformity, and percentile analyses to determine appropriate dimensions. Three conceptual designs were evaluated through a weighted decision matrix, and Concept 2 — a flat-platform trolley with stainless steel frame, ergonomic angled handle, and wheel locking stopper — was selected. The final design dimensions are: handle height 72 cm, platform width 45 cm, platform depth 85 cm, and wheel diameter 4 inches. Safety analysis using the Rapid Entire Body Assessment (REBA) method estimated a risk score of 3–5, indicating low to medium risk. Economic feasibility analysis using Net Present Value (NPV) and Payback Period (PP) methods yielded NPV = Rp 2,486,767 (NPV > 0) and PP = ±11 months, confirming financial viability. The manufacturing cost of Rp 707,400 is 29.4% lower than comparable commercial products, while offering enhanced safety features. This study demonstrates a replicable, data-driven framework for ergonomic tool design in SMI contexts.